Drying of solid Materials by vacuum Fluidized Bed Dryer - I. Abdul Wahab, Majid; H. Rheima, Khalid. (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
In the present study the performance of drying process of dffirent solid materials by batch fluidized bed drying under vacuum conditions was investigated. Three, different solid materials, namely; ion exchange resin-8528, aspirin and paracetamol were used. The behavior of the drying curves as well as the rate of drying of these materials had been studied. The experiments were caried out in a 0.0381 m column diameter fluidized by hot air under yacuum conditions. Four variables affecting on the rate of drying were studied’ these variables are vacuum pressure (100 - 500 mm Hg), air temperature (303-323 K), particle size (0.3-0.8 mm) and initial moisture content (0.35-0.55 g/g solid)-for resin and (0.1-0.2 g/g soltid) for aspirin and paracetamol. The study of the characteristics of the drying curves showed that the drying behavior depends mainly on the type of the solid material and on the operating conditions. It was found that the drying rate at vacuum conditions is enhanced by increasing the operating temperature of the air and decreases by increasing the initial moisture content of the material and the particle size. Moreover, an experiment was carried out to study the drying of aspirin solid material which is dried in atmospheric fluidized bed dryer operating at the same conditions to compare the temperature and time needed in both techniques. It was found that the temperature needed for vacuum fluidized bed dryer (303 K) is less than needed by fluidized bed dryer operating at atmospheric pressure (323 K). A simpliled model’for the drying of solids in the constant-rate period in a batch fluidized bed is developed, considering the bed to consist of dense phase and bubble phase with heat and mass transfer between the phases. It is assumed that the solids in dense phase to be in thermal equilibrium with the interstitial gas in the dense phase. The bubble size, its rise velocity, and the bubble volume fraction are taken into account while developing the model. The model is compared with experimental data reported in this study and found to match satisfactorily.